PELATIHAN MEDIA PEMBELAJARAN DIGITAL UNTUK GURU PAUD DI KABUPATEN DONGGALA - Agusniatih, Andi; Durrotunnisa, Durrotunnisa; Awalunisah, Sita; Imamah, Zakiyyatul; Amrullah, Amrullah (Yayasan Penelitian dan Inovasi Sumatera (YPIS), 2025)
Early childhood learning media is very important to be prepared by teachers before learning activities begin. Without learning media as an introduction or intermediary, ongoing learning will not be interesting. The use of technology will make it very easy for teachers to prepare practical and interesting digital-based learning media. Creating digital-based learning media will allow teachers to be creative and innovate with various applications and devices provided by information technology. Learning or media created by utilizing digital-based learning provides a new revolution for teachers in the learning methods used. The digital media used include PowerPoint, Prezi, Canva, CapCut, and the Kahoot and Quizizz apps, making learning more enjoyable. Regular use of digital media can improve learning quality, as students become accustomed to learning in a more engaging, active, and independent manner. Furthermore, this method helps students develop 21st-century skills such as digital literacy, critical thinking, collaboration, and creativity. This also makes it easier for teachers to assess, provide feedback, and adapt teaching methods to meet students' needs. The results of community service found a significant increase in teacher knowledge and skills with an average pre-test score of 61 and an average post-test score of 83. This activity succeeded in increasing teacher competence in preparing the learning process.